2006
DOI: 10.1177/1049732305286051
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Physical Activity Participation Among High- and Low-SES Youth

Abstract: Researchers have rarely addressed the relationship between socioeconomic status (SES) and physical activity from the perspective of youth. To illuminate the factors that youth from low and high-SES areas consider important to increase physical activity participation among their peers, 160 youth (12-18 years) participated in small focus group interviews. Guiding questions centered on the general theme, "If you were the one in charge of increasing the physical activity levels of kids your age, what would you do?… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
190
1
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(218 citation statements)
references
References 27 publications
14
190
1
8
Order By: Relevance
“…As a percentage of total park users more young people were observed in Eastern than Southville moreover, those observed were marginally more moderately active and fewer sedentary. Results may indicate greater reliance on low cost recreation facilities in deprived areas which is in line with Canadian findings (Pabayo et al, 2011;Castonguay and Jutras, 2009;Humbert et al, 2006). Furthermore, there were more 11-15 than 16-20 year old park users which may indicate preference for low cost socialisation and recreational activities in younger adolescents however, without leisure activity data from young people postulations remain supposition.…”
Section: Urban Park Facilitation Of Park Use and Physical Activitysupporting
confidence: 77%
“…As a percentage of total park users more young people were observed in Eastern than Southville moreover, those observed were marginally more moderately active and fewer sedentary. Results may indicate greater reliance on low cost recreation facilities in deprived areas which is in line with Canadian findings (Pabayo et al, 2011;Castonguay and Jutras, 2009;Humbert et al, 2006). Furthermore, there were more 11-15 than 16-20 year old park users which may indicate preference for low cost socialisation and recreational activities in younger adolescents however, without leisure activity data from young people postulations remain supposition.…”
Section: Urban Park Facilitation Of Park Use and Physical Activitysupporting
confidence: 77%
“…However, in the focus groups of Humbert et al, low-SES adolescents reported that social support was essential to engage in PA (7) . Comparison with other studies was not possible as no other study has investigated the possible mechanisms through which SES differences in PA remain.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are in accordance with previous work, showing that low family affluence was associated with lower physical activity levels and increased hours of television viewing, for both boys and girls (40,41) . Personal and environmental parameters, such as safety, affordability and social support, may influence the aforementioned inequalities (42) . Taking into account that engagement in sedentary activities tends to be associated with unhealthier dietary choices (43) , combined diet and physical activity interventions should be implemented in order to target a healthy lifestyle pattern.…”
Section: Discussionmentioning
confidence: 99%